Efficacy, safety, and cost-effectiveness analysis of aflibercept in metastatic colorectal cancer: A rapid health technology assessment - Ge, Pu; Wan, Ning; Han, Xiao; Wang, Xinpei; Zhang, Jinzi; Long, Xiaoyi; Wang, Xiaonan; Bian, Ying (Frontiers in Pharmacology, 2022)
Objective： To evaluate the efficacy, safety and cost-effectiveness of aflibercept for the treatment of mCRC in order to provide decision-making reference for the selection of targeted drugs for second-line treatment of mCRC in Hong Kong, Macao and Taiwan regions of China and the selection of new drugs for medical institutions in these regions. Methods： A systematic retrieve on databases including PubMed, Embase, Cochrane Library, China national knowledge infrastructure (CNKI), Wanfang, Weipu, as well as relevant websites and databases of health technology assessment including the National Institute of Health and Clinical Optimization, the Centre for Evaluation and Communication at the University of York and the Canadian Agency for Medicines and Health Technology, was conducted. The literature was screened according to the inclusion and exclusion criteria, and the data was extracted and analyzed by two authors, while the quality of the literature was assessed. Results： Finally, we included 2 HTA reports, 11 systematic reviews/Meta-analyses, and 2 cost-effectiveness studies in the rapid health technology assessment. For mCRC patients receiving second-line treatment, aflibercept combined with FOLFIRI significantly increased progression-free survival (PFS) and overall survival (OS), and the objective remission rate (ORR) also improved, compared with folinic acid+fluorouracil+ irinotecan (FOLFIRI). In terms of safety, mCRC patients who received aflibercept combined with FOLFIRI therapy had a higher incidence of grade 3-4 adverse events than those who received FOLFIRI alone, including anti-VEGF-related adverse events (hypertension, hemorrhagic events and proteinuria) and chemotherapy-related adverse events (diarrhea, weakness, stomatitis, hand-foot syndrome, neutropenia, and thrombocytopenia). In terms of cost-effectiveness, two economic studies conducted in the UK and Japan respectively found that compared with FOLFIRI, aflibercept combined with FOLFIRI had no cost-effectiveness advantage in mCRC patients receiving second-line treatment. Conclusion： Compared with FOLFIRI treatment, aflibercept combined with FOLFIRI for the second-line treatment of mCRC patients has better efficacy, worse safety and is not cost-effective. More high-quality clinical studies are required for further exploration of aflibercept’s clinical value. Medical institutions in Hong Kong, Macao and Taiwan regions of China should be cautious when using or introducing aflibercept plus FOLFIRI as a mCRC treatment.